F(x)=sqrt(x+3)

Simple and best practice solution for F(x)=sqrt(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=sqrt(x+3) equation:


Simplifying
F(x) = sqrt(x + 3)

Multiply F * x
xF = sqrt(x + 3)

Reorder the terms:
xF = qrst(3 + x)
xF = (3 * qrst + x * qrst)
xF = (3qrst + qrstx)

Solving
xF = 3qrst + qrstx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1qrstx' to each side of the equation.
-1qrstx + xF = 3qrst + qrstx + -1qrstx

Combine like terms: qrstx + -1qrstx = 0
-1qrstx + xF = 3qrst + 0
-1qrstx + xF = 3qrst

Reorder the terms:
-3qrst + -1qrstx + xF = 3qrst + -3qrst

Combine like terms: 3qrst + -3qrst = 0
-3qrst + -1qrstx + xF = 0

The solution to this equation could not be determined.

See similar equations:

| 4.10(x-5)=-80 | | 420n^4-708n^3+168n^2=0 | | 1/3x^11x-4=0 | | 3x+2y+4z=9 | | ln(2x+3x^2)=3 | | 5(-2x-8)=-30 | | 2.7(x+8)=49 | | 70n^4-118n^3+28n^2=0 | | -3+7x=-x+93 | | X-2b= | | 209x-152=19(11x-8) | | 7m-4=11 | | -5x-2=-24+6x | | 5(20-1.6x)=100 | | 5y+8x=100 | | 65x/8 | | x+8=-4x+68 | | 8w/8=65x/8 | | 400=14.814x+6.8 | | 6x+8=-7x-109 | | n/8​​=​11/5​​ | | 18(t-6)+3t=7(3t+4)-8 | | 3x-94=36x+38 | | 2t^3-3t+1=0 | | 3v^3+21v^2-54v=0 | | x-6=-7x-30 | | Y=4x^3+x-5 | | p^3-4p^2-60p=0 | | n-12*10=12 | | 3(p-2)=2(p+6) | | Ln(x-8)=4 | | 25n^6+80n^3+64=0 |

Equations solver categories